Deflating Deflationary Truthmaking. (22nd July 2019) - Asay, Jamin; Baron, Sam
Abstract: In this paper we confront a challenge to truthmaker theory that is analogous to the objections raised by deflationists against substantive theories of truth. Several critics of truthmaker theory espouse a 'deflationary' attitude about truthmaking, though it has not been clearly presented as such. Our goal is to articulate and then object to the underlying rationale behind deflationary truthmaking. We begin by developing the analogy between deflationary truth and deflationary truthmaking, and then show how the latter can be found in the work of Dodd, Hornsby, Schnieder, Williamson, and others. These philosophers believe that the ambitions of truthmaker theory are easily satisfied, without recourse to ambitious ontological investigation—hence the analogy with deflationary truth. We argue that the deflationists' agenda fails: there is no coherent deflationary theory of truthmaking. Truthmaking, once deflated, fails to address the questions at the heart of truthmaking investigation. Truthmaking cannot be had on the cheap.